MEDETOMIDINE HYDROCHLORIDE EFFICIENCY AND SAFETY IN GUINEA PIG (Cavia porcellus), IN DOSES ESTIMATED THROUGH ALLOMETRIC EXTRAPOLATION - Poleze, Evandro; Brunson, David; Giovanelli, Diogo Fernandes; Conti, Juliano Bortolo De; Wosiacki, Sheila Rezler; Belettini, Salviano Tramontin; Pachaly, Evandra Maria Voltarelli; Pachaly, José Ricardo (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2015)
In this study, medetomidine hydrochloride, an alfa2 adrenergic receptor agonist, was administered to five adult guinea pigs (three males and two females) to verify the efficiency and safety of using doses calculated by using an allometric scale. A surgical procedure was performed to insert a polyethylene cannula that advanced 2.0 to 2.5 cm into the left carotid artery until the aorta. A minimum recovery period of two days was observed before any other manipulation or pharmacological test were performed. The cannulas were washed every two days with heparinized saline flow and remained patent for two to three weeks after insertion. After surgery, each animal was placed in an open box measuring 45x25x20cm, in a quiet room with soft lighting. The “MS” group received exactly the allometrically calculated dose, while the “2MS” group received twice the allometric dose and the “½ MS” group received half the allometric dose. Parameters were measured and analyzed at 0, 5, 10, 20, 40, 60, 90 and 120 minutes after injection. Body mass was 709.6±169g, 742±172.87g and 710±160.2g for groups 1, 2 and 3, respectively. Body temperature was 101.68±0.19ºF; respiratory rate was 85.2±4.54 strokes per minute; heart rate was 297.13±3.46 beats per minute; PaO2 at 81.7±9.43mmHg; PaCO2 at 34.49±1.59mmHg; pH was measured at 7.41±0.07; hematocrit at 38.4±1.31%; total protein was 4.33±0.29g/dL, glucose was measured at 97.13±3.75mg/dL; systolic blood pressure was 85.53±2.50mmHg; diastolic pressure at 7.,40±3.74mmHg; and mean blood pressure was 78.73±1.13mmHg. Straightening postural reaction was lost at 7.20±2.05, 12.80±3.56 and 8.67±3.06 minutes for groups “2MS, MS and ½ MS”, respectively. Awakening time was 53.80±7.19, 67.20±5.54 and 55.67±11.06 minutes for groups “2MS, MS and ½ MS”, respectively. For the MS group, chemical restraint was considered “excellent” with “poor” analgesia, and for the 2MS group, it was considered “good”, also with “poor” analgesia. This means these protocols should be used for painless procedures when immobilization is necessary. The ½ MS protocol is not suitable for chemical restraint in guinea pigs. This paper presents new results obtained from research conducted in 2000.